Linguagem e surdez: a coesão em textos de surdos - Silva, Ayonan Santos e (2014)
In this dissertation we use a methodology that explores the level of writing comprehension of deaf considering the analysis of texts written in a test to get a job to describe mechanisms of textual cohesion used by them. This study is based on a descriptive research, which intend to demonstrate the characteristics of a particular social segment to interpret a particular form of behavior. We do not intend to interfere on the reality that was observed neither modify it, at least not within the limits of this dissertation, which is exploratory. On this research, which is configured as qualitative, we are searching for meanings from assumptions and considerations of authors that deal with aspects of Portuguese and Libras. Therefore, we are not concerned about sample quantity, but rather about the evidences observed by reading the texts. With regard to the sample chosen for analysis, three texts produced by Brazilian deaf persons, submitted to a test to get a job in an insurance company, show differences in linguistic structure of texts well-written by Portuguese speakers that are not deaf persons. It was possible verify that the texts produced by deaf persons, despite having formal problems, do not disregarded the principle of coherence. However, the fact that the coherence did not be affect does not mean that the surface structure should not be organize according to the rules of the Portuguese written language, because in a society the knowledge of standard written language becomes crucial to facilitate the interaction and social insertion, especially in the corporate world. The listener that ignores the reality of the deaf assumes that this writer has Portuguese as unique and/or native language. Once that the perception of the deaf is primarily visual, he has restricted access, or no access, to the oral modality of the Portuguese, the listener is surprised by the fact that the scholarly deaf demonstrate such a restrict command of the Portuguese. Informed that the deaf student has sign language at his disposal and that, in school and in interactions situations, he deals with sign language of non native speakers, with Portuguese signs, lip reading, gestures, visual information and other strategies that can assist him in acquiring oral language, it is hard to believe that the Portuguese language is so opaque to the deaf or that years of schooling have no expected effect on him. To support the analysis of the corpus and to show how the deaf write texts using cohesion strategies, we are based on authors linked to the textual linguistics as Fávero (1999) and Koch (1995). We also work with the concept of retextualization (Marcuschi, 2000). By the analysis of the corpus, we observed a progress of the deaf in the construction of coherent and cohesive texts. Considering a profound knowledge of Libras acquired by the teacher, as well as interactional exchanges with scholars, the deaf can develop written in Portuguese and can be able to write well-structured, clear and meaningful texts